A review of principles in design and usability testing of tactile technology for individuals with visual impairments. Issue 1 (2nd January 2017) - Horton, Emily L.; Renganathan, Ramkesh; Toth, Bryan N.; Cohen, Alexa J.; Bajcsy, Andrea V.; Bateman, Amelia; Jennings, Mathew C.; Khattar, Anish; Kuo, Ryan S.; Lee, Felix A.; Lim, Meilin K.; Migasiuk, Laura W.; et al.
ABSTRACT: To lay the groundwork for devising, improving, and implementing new technologies to meet the needs of individuals with visual impairments, a systematic literature review was conducted to: a) describe hardware platforms used in assistive devices, b) identify their various applications, and c) summarize practices in user testing conducted with these devices. A search in relevant EBSCO databases for articles published between 1980 and 2014 with terminology related to visual impairment, technology, and tactile sensory adaptation yielded 62 articles that met the inclusion criteria for final review. It was found that while earlier hardware development focused on pin matrices, the emphasis then shifted toward force feedback haptics and accessible touch screens. The inclusion of interactive and multimodal features has become increasingly prevalent. The quantity and consistency of research on navigation, education, and computer accessibility suggest that these are pertinent areas of need for the visually impaired community. Methodologies for usability testing ranged from case studies to larger cross-sectional studies. Many studies used blindfolded sighted users to draw conclusions about design principles and usability. Altogether, the findings presented in this review provide insight on effective design strategies and user testing methodologies for future research on assistive technology for individuals with visual impairments.